Effect of obesity on molecular characteristics of invasive breast tumors: gene expression analysis in a large cohort of female patients. Issue 1 (December 2016) - Toro, Allyson; Costantino, Nicholas; Shriver, Craig; Ellsworth, Darrell; Ellsworth, Rachel
Abstract Background Obesity is a risk factor for breast cancer in postmenopausal women and is associated with decreased survival and less favorable clinical characteristics such as greater tumor burden, higher grade, and poor prognosis, regardless of menopausal status. Despite the negative impact of obesity on clinical outcome, molecular mechanisms through which excess adiposity influences breast cancer etiology are not well-defined. Methods Affymetrix U133 2.0 gene expression data were generated for 405 primary breast tumors using RNA isolated from laser microdissected tissues. Patients were classified as normal-weight (BMI < 25), overweight (BMI 25–29.9) or obese (BMI ≥ 30). Statistical analysis was performed by ANOVA using Partek Genomics Suite version 6.6 using a false discovery rate <0.05 to define significance. Results Obese patients were significantly more likely to be diagnosed ≥50 years or with African American ancestry compared to lean or overweight women. Pathological characteristics including tumor stage, size or grade, lymph node status, intrinsic subtype, and breast cancer mortality did not differ significantly between groups. No significant gene expression differences were detected by BMI in a non-stratified analysis which included all subtypes or within luminal B, HER2-enriched or basal-like subtypes. Within luminal A tumors, however, 44 probes representing 42 genes from pathways such as cell cycle, p53 and mTOR signaling, DNA repair, and transcriptional misregulation were differentially expressed. Conclusions Identification of transcriptome differences in luminal A tumors from normal-weight compared to obese women suggests that obesity alters gene expression within ER+ tumor epithelial cells. Alterations of pathways involved in cell cycle control, tumorigenesis and metabolism may promote cellular proliferation and provide a molecular explanation for less favorable outcome of obese women with breast cancer. Targeted treatments, such as mTOR inhibitors, may allow for improved treatment and survival of obese women, especially African American women, who are more likely to be obese and suffer outcome disparities.